Features of the Formation of the Architecture of Residential Buildings in the Regions of Uzbekistan - Moxinur Xolmuminqizi Sherqulova; Zafarbek Erkinovich Matniyazov; Akhror Jabbarovich Abdullaev (Genius Journals, 2022)
This article is devoted to Uzbek folk architecture, its diversity, originality, its value for modern construction. Differences in historical and natural-climatic conditions, which led to the localization of individual cultural centers, are considered. These factors led to the parallel existence of several schools of folk architecture, each of which has its own specific features, each has its own special building and artistic traditions. Being united in general design and spirit, the folk architecture of Uzbekistan is divided into a number of local schools.
Keywords: types of Uzbek dwellings; natural and climatic conditions; dwelling feature; Khorezm